Ar kultūra ir jos socialinė aplinka nulemia žmogaus elgsenos suvokimą siekiant tikslo? - Putniņa, Margarita (Information & Media, 2008)
Pasirinktas tyrimo aspektas yra svarbus edukacinei veiklai. Mokslininkai, jį tyrinėję anksčiau (Weiner, Bar-Tal, Brophy ir kiti), skatina universitetų dėstytojus padėti studentams susikurti tinkamą aplinką, galinčią turėti įtakos jų pasiekimams ir poveikį jų elgsenai. Tai padėtų išvengti akademinių nesėkmių. Praktinis tyrimas atskleidė, koks yra studentų kasdienis indėlis siekiant akademinių laimėjimų ar patiriant nesėkmę. Klausimas buvo tiriamas pateikus neviešinamus individualius klausimus. Panašūs tyrimai buvo atlikti ir LU A, Latvijos universitetuose ir Talino universitete. Estijoje buvo siekiama palyginti, kiek kultūrinė aplinka ir kalba gali paveikti, lemti studentų mąstymą ir veiksmus, taip pat komunikacijos procesus. Antroji tyrimo dalis pristato giluminius interviu, kuriuos taikant buvo apklausti 6 universitetų dėstytojai. Viena vertus, dėstytojai sutaria, kad latviai yra egocentriška tauta, bet, kita vertus, jie yra atviresni tarpasmeniniam dialogui nei estai.Do culture and its social environment determine humans’ perception of their achievement related behaviour?Margarita PutniņaSummaryThe chosen research topic is valuable for educational practice. Scientists who have researched it (Weiner, Bar-Tal, Brophy, et al.) encourage university teachers to help students create appropriate attributions for their achievement-related behaviour, preventing failure in academic activities. In the practical research, students’ causal attributions of their academic success and failure were studied using open-ended questions. A similar research was done half a year ago in LUA, Latvia and Tallinn University, Estonia in order to compare how the cultural environment and language influence the students’ way of thinking and acting, including the process of communication.The most prevailing cause of failure in students’ answers was ‘other people’, like in the previous research (44% now, 53% before), but as regards success internal causes prevailed (55% now, 55% before).The category of interaction still remained a rather important factor in both the case of success and the case of failure (success 11.7% and to failure 17% now, success 18% and failure 21% before).The sign of self-serving bias was affirmed again.The second part of practical research consisted of the analysis of material obtained by deep interviews with six university teachers involved in teaching the students-respondents. On the one hand, teachers consider Latvians to be an ego-centred nation, but on the other hand, they are more open than Estonians to interpersonal dialogue.Key words: causal attributions, self-serving bias, academic achievements, students, teachers